Islamic Religious Education and Students’ Social Ethics - Muhammad Ibnu Soleh (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2026)
This study aims to analyze the relationship between Islamic Religious Education and students’ social ethics in schools. Social ethics is an important aspect of students’ character development because it influences how individuals interact with others respectfully, responsibly, and cooperatively in social environments. In the modern era, many students face ethical challenges such as bullying, dishonesty, intolerance, disrespectful communication, and negative social media influences. Therefore, Islamic Religious Education is considered important in strengthening students’ moral awareness and social behavior through the implementation of Islamic values. This research employed a quantitative approach using a survey research design. The population of the study consisted of students at a selected school, while the sample was determined using purposive sampling techniques. Data were collected through questionnaires, observations, and documentation. The questionnaire used a Likert scale to measure students’ perceptions regarding Islamic Religious Education and social ethics. The collected data were analyzed using descriptive statistics and simple linear regression analysis. The findings revealed that Islamic Religious Education has a positive and significant influence on students’ social ethics. Students who actively participated in religious learning activities demonstrated better honesty, discipline, empathy, cooperation, tolerance, responsibility, and respect toward others. Teachers, religious activities, and supportive school environments also contributed significantly to strengthening students’ ethical awareness and social behavior. However, several challenges such as peer pressure, low learning motivation, social media influences, and limited innovation in teaching methods were still identified. Therefore, schools are encouraged to improve Islamic Religious Education learning through interactive teaching strategies, technology integration, and stronger collaboration among teachers, parents, and communities. Overall, this study concludes that Islamic Religious Education plays an essential role in developing students with strong social ethics, positive moral character, and responsible behavior in modern society.